Influence of educational messages, delivered in nominal focus groups, on dairy purchasing and consumption behavior of inadequate dairy consumers - Myers, Jack Steven (Kansas State University, 2022)
With the decline in fluid milk consumption, combined with nearly 90% of the U.S. population not consuming enough dairy (≤ 3 cups equivalent daily), there is growing interest in increasing dairy foods consumption amongst this inadequate dairy consumer (IDC) population. The objective of this study was to quantify the effectiveness of educational messages (EM), delivered in nominal focus groups (NFGs), to 1) increase dairy purchasing and 2) increase dairy consumption of IDC. Research participants were identified using a Food Choices and Intolerances (FCI) survey, with panelists recruited from the greater Manhattan, KS, USA area. Inadequate dairy consumers (n=101) were recruited to attend an NFG and received a primary EM or a combination of a primary and secondary EM. Secondary EM contained information relating to one of three different dairy foods nutritional topics. Panelists who received only the primary EM (n=15) were given an educational message in reading nutrition facts panels, while panelists who received the primary and a secondary EM also received one of the three secondary EM (n=65): lactose maldigestion (n =17), nine essential nutrients (n=20), or prebiotics and probiotics (n=28 ). During the NFG, panelists were asked to self-report their dairy purchasing and consumption behavior. One month after completion of the NFG, panelists were asked to complete a follow-up survey where they self-reported dairy purchasing and consumption in the time since receiving an EM. After data were collected, categorical responses on dairy foods purchasing and consumption were converted to servings/week/person. Using a Wilcoxon signed-rank test, the differences in servings/week/person were analyzed to determine significant differences in dairy foods (milk, yogurt, cheese, and ice cream) purchased and consumed before and one month after receiving an EM. Overall, this study found that the primary EM had little effect on increasing the purchasing of dairy foods but did have a significant effect (p < 0.05) on dairy foods consumption. When secondary EM were analyzed individually, the prebiotics and probiotics EM had a significant effect on dairy purchasing and consumption, whereas the lactose maldigestion EM only had a significant effect on increasing dairy foods consumption. The nine essential nutrients of milk message had no significant effect on dairy foods purchasing or consumption.
Keywords: Consumers; Focus groups; Social marketing; Dairy foods; Educational messages